Implementation of the Angso Duo Market Relocation Policy in Jambi City in the Perspective of Traders - Samsuddin Samsuddin; Budiman Rusli; Utang Suwaryo; Dede Sri Kartini; Suryawahyuni Latief (Green Publisher Indonesia, 2022)
This study aims to describe the implementation of the Jambi city government's policy regarding the relocation of Angso Duo Market in the perspective of Angso Duo market traders in Jambi City. This study uses a descriptive method with a qualitative approach, data sourced from primary data and secondary data. Data collection was carried out through observation by observing the activities of Angso Duo Market traders, interviews with Jambi city trade officials and traders, and documents in the form of government regulations, literature and other documents that support this research. Data is processed through data presentation, data reduction, drawing conclusions, and recommendations. The results showed that the implementation of the Angso Duo traditional market relocation policy from the perspective of traders, namely: additional costs incurred by traders to rent new kiosks at Angso Duo market with kiosk rental costs being more expensive than before, and costs to pay for the arid transportation costs from Pal 10 (a place for loading and unloading goods in bulk) to the new Angso Duo market location; and nd a decrease in revenue due to a decrease in the number of customers due to the emergence of a buffer market due to the location of the Angso Duo market which is far from the main road, and the difficulty of customers l finding the merchant market